Role of Technology in the Development of Smart and Secure Public Voting Systems – a Review of Literatures - Vinayachandra; Geetha Poornima K; Rajeshwari M; Krishna Prasad K (International Journal of Management, Technology and Social Sciences (IJMTS), 2020)
The goal of the election is not only to determine the outcomes but also to lend credence to the winners, even for those voters who did not bother voting for them. This underlines the necessity of holding free, fair, and hidden elections. Component of all this is that elections are controlled by open and accountable, neutral, and autonomous electoral-management bodies. Utilizing technology in voting procedures can make it quicker, more efficient, and less susceptible to security breaches. The technology can ensure the safety of every vote, better and faster and much more accurate counting and automatic tallying. The design of a sophisticated voting system is a complex task as it has to fulfill several essential criteria. The secrecy of an elector’s poll is to be well-preserved. The voting system should not give any evidence that proves which candidate receives a particular voter’s vote. The process uses minimum paper documents and is therefore environmentally friendly. Bio-metric or retina scans can be used to ensure security. The e-voting system is vulnerable to several serious attacks from external sources. There is indeed a likelihood that anybody who has immediate access to the e-voting system can access it suspiciously. Malevolent software can steal one candidate’s votes and assign them to some other. An attacker may deny officials access to the e-voting arrangement or render an e-voting structure unavailable for the Election Day voting process. This is known as a service denial (DoS) attack. But this kind of threat is hard to detect. A large number of questionable and invalid votes are the big problem with traditional paper-ballot based voting system. This phenomenon will be eliminated if the e-voting system is used. In addition to the speed of counting and reduction of errors the e-voting system offers some more advantages such as accessibility, verifiability, and availability. When the e-voting system is integrated with the Internet, any eligible voter can vote from anywhere as there will be two or more levels of authenticity checks. In this paper, the authors reviewed the application of technology in the development of smart, secure, and versatile public voting systems. Also, they outlined research gaps and recommend new approaches to the existing systems.